Power quality monitoring and analysis of aerodrome supply system: A study in Gautam Buddha International Airport, Nepal - Neupane, Bishnu Prasad (Journal of Engineering Issues and Solutions, 2023)
The power supply system may contain disturbances leading to variations in voltage and frequency from their nominal value, non-sinusoidal waveform injection, presence of negative and zero sequence components, etc. Power quality is a measure of characteristic disturbances present in the power supply which ensures the importance of quality of service and consumer requirements. Electrical equipment installed in an aerodrome is more sensitive and prone to disturbance present at the power supply end. This study provides results of a theoretical power flow study, power quality monitoring, quality analysis, and probable remedies for power quality issues in an aerodrome electrical supply system in Nepal. Power quality measurement for supply from the utility here, Nepal Electricity Authority, and internal power generations in Gautam Buddha International Airport (GBIA) Siddharthanagar, Rupandehi, Nepal is performed by using theoretical load flow approach and continuous monitoring using a power data analyzer. The scope and origin of various disturbances which may induce power quality issues are analyzed. It is observed that the power supply at GBIA has voltage fluctuations of about ±12% and total voltage harmonic distortion of 6.5% with the presence of negative and zero sequence components. A remedial solution for the power quality problem is proposed for future enhancement of the electrical supply system at GBIA.